Serum iron level shortly after iron supplementation shortly after and 2 hours after meal in women with iron deficiency anemia - Sri Kadarsih Soejono,,Lukman Hakim, ErnaKristin, Muhammad Hakimi (Journal of the Medical Sciences (Berkala Ilmu Kedokteran), 2009)
Background: Incidence of anemia in women in developing countries is still high, that is, around 43%. This incidence rate is far more higher that that in industrial countries, which is ranged between 10-12 %. The prevalence of iron deficiency anemia is still high, particularly in developing countries. The cause of the high prevalence of iron deficiency anemia is not known, since it involves various factors. Two of the probable etiologic factors is variability in dosage administration, and the effect of co-administered food. Studies on the pharmacokinetic of iron after single dose iron tablet administration in women with anemia and pharmacokinetic of iron coadministered with food in healthy women have been done, but study on repeated dose has never been conducted. Objective: To understand serum iron level after ingestion of repeated dose of iron shortly after and 2 hours after meal for 12 weeks in women with iron deficiency anemia. Method: The research design was a fase II clinical trial. Subjects were 24 women with iron deficiency anemia, classified into two groups, who were treated as follows: the first group was consisted of 12 women with iron deficiency anemia, treated with twice-a-day ferrous sulphate tablet @ 300 mg orally, given shortly after meal for 12 weeks; the second group was consisted of 12 women with iron deficiency anemia, treated with twice-a-day ferrous sulphate tablet @ 300 mg orally, given 2 hours after meal for 12 weeks. Blood samples were taken in week 2,4, 6, 8, 10, and 12 after treatment. Serum (ferric) iron level was measured with Vitros Fe Slides method. Result: Minimum, maximum, and average steady-state iron levels (Css min, Css max, Css average) of treatment 1 were 108,78:t 13.79 ug/dL, 121 .44:t 15.79 ug/dL, and 115.11 :t 13.13 ug/dL (mean:t SEM), respectively; while minimum, maximum, and average steady-state iron levels (Css min, Css max, Css average) of treatment 2 were 115.15 :t 46.27 ug/dL, 141.36:t 61.36 ug/dL, and 124.92:t 53.43 ug/dL (mean:t SEM), respectively. No statistical significant difference were found within treatment in minimum steady-state level between week 2, 4, 6, 8, 10, 12 after treatment. There was also no significant difference in minimum steady-state level between treatment group in week 2, 4, 6, 8, 10, and 12. , Conclusion: There were no differences inserum iron level after ingestion of repeated dose of iron shortly after and 2 hours after meal for 12 weeks in women with iron deficiency anemia. Key Words: iron supplementation-serum iron-iron deficiency anemia-steady-state iron level